Human recessive osteopetrosis - Helfrich, M.; Perdu, B.; Coxon, F. (Osteologie, 2009)
Osteopetrosis is an inherited high bone mass condition resulting from reduced osteoclast activity. Over the past ten years, many of the genes mutated in the various forms of osteopetrosis have been identified. It has become clear that there are not only dominant and recessive forms, but also that within the recessive forms subsets exist, classified as osteoclast-rich and osteoclast-poor. Here, we review the different genetic mutations that are known to cause osteopetrosis and then focus specifically on recessive types of the disease. We will illustrate how not only genetic analysis is important, but also that functional osteoclast assays in the laboratory, combined with bone histology, can help to come to a precise diagnosis. We then discuss how this rare condition has led to new insights in the complex process of bone resorption by osteoclasts. Our story is one of bedside to bench and back again.
Keywords: Osteopetrosis; osteoclast; acidification; endosomal trafficking